Le père ou le roi : Stratégies de traduction en Ésaïe IX, 6 et XXII, 21 (Septante) - Philippe Le Moigne (Cahiers d'Études du Religieux- Recherches Interdisciplinaires)
The Septuagint (the former Greek translation of the Hebraic Bible) of Isaias refuses twice to a person the name « father » which the Hebrew text gave him; at the same time, it creates for these people royal features, or stresses them. It is possible that the translator wanted to avoid attributing to a human being the honorary term of « father », that he would so reserve for God.